ダイ52ジ ニホン ナンキョク チイキ カンソクタイ ナツタイ ニ オケル トウキョウカイヨウダイガク ウミタカマル カンソク ホウコク - 橋田, 元; ハシダ, ゲン; 佐々木, 洋; ササキ, ヒロシ; 北出, 裕二郎; キタデ, ユウジロウ; 小達, 恒夫; オダテ, ツネオ; Hashida, Gen; Sasaki, Hiroshi; Kitade, Yujiro; Odate, Tsuneo (2012)
P(論文) 第52次日本南極地域観測隊(JARE-52)では,南極地域観測第VIII期6か年計画(平成22-27年度)の第1年次として重点研究観測及び一般研究観測の課題を実施するため,東京海洋大学練習船「海鷹丸」の南極海航海おいて海洋観測を実施した.主として,南極海の温暖化,大気中二酸化炭素濃度増加に伴う海洋酸性化などの変化が生態系に与える影響,及びプランクトン群集組成の変動と環境変動との関係の解明を目指すことが目的である.今回の観測航海は,「海鷹丸」の平成22年度遠洋航海UM-10-04のうち,フリーマントル─ホバート間(2010年12月24日～2011年1月22日)において,東経110度線,東経140度線を中心とした二つの海域で行われた.特に,東経110度の南緯57度～62度においては,「海鷹丸」観測に加え, 2010年12月初旬及び2011年3月初旬に「しらせ」が同一海域で観測を行い,時系列観測となっている. A marine science cruise was undertaken during December 2010 and January 2011 on board the Research and Training Vessel Umitaka-Maru, operated by Tokyo University of Marine Science and Technology (TUMSAT), to accomplish projects of the six-year plan Phase VIII of the Japanese Antarctic Research Expeditions (JARE-52 to -57). The projects and the cruise were planned to investigate the responses of Antarctic marine ecosystems to environmental changes related to global warming and oceanic acidification, and to study plankton community structure and environmental parameters. One of the main aims of the projects was to clarify the life cycle and physiology of plankton with shells of calcium carbonate (e.g., pteropods and coccolithophores), because these plankton are regarded to be the most sensitive to oceanic acidification. We performed net castings to qualitatively estimate the vertical distribution of plankton, made hydrographical observations, took measurements of dissolved inorganic carbonates in seawater, deployed a year-around mooring with sediment traps, made observations of a surface drifting buoy with a sediment trap and sensors to measure environmental parameters, and performed onboard acidified culture experiments using pteropods. The RT/V Umitaka-Maru departed from Fremantle, Australia, on 24 December 2010, cruised to the study area around the marginal sea ice zone (along 110°E and 140°E), and returned to Hobart, Australia, on 22 January 2011. The cruises by the icebreaker Shirase (JARE-52) in December 2010 and March 2011 followed the same study area as that described above, along 110°E, in order ...